2018
DOI: 10.1084/jem.20180147
|View full text |Cite
|
Sign up to set email alerts
|

IL1RAP potentiates multiple oncogenic signaling pathways in AML

Abstract: IL1RAP is an emerging target for AML therapy. Studying its cell-intrinsic function revealed that IL1RAP interacts with and amplifies signaling through c-KIT and FLT3 in AML cells. This novel promiscuous role of IL1RAP in AML has implications for therapeutic targeting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 70 publications
3
65
0
1
Order By: Relevance
“…The elevated responsiveness of IL-1b-sensitive AML bone marrow cells appeared to correlate with a significantly increased expression of IL-1R1 and IL-1RacP compared to IL-1b non-sensitive AML samples, consistent with other findings demonstrating that expression of IL-1RAcP is a prognostic marker of AML [91][92][93]. In addition to relaying growth signals from IL-1 cytokines, a recent study suggested a broader role for IL-1RAcP in AML by amplifying oncogenic AML pathways through recruitment of the tyrosine kinases FLT3 and c-KIT in AML cells [92]. This suggests that therapeutic neutralization of IL-1RacP may permit to simultaneously target multiple oncogenic pathways in AML.…”
Section: Anti-tumorigenic Role Of Il-1b In Solid Tumourssupporting
confidence: 88%
“…The elevated responsiveness of IL-1b-sensitive AML bone marrow cells appeared to correlate with a significantly increased expression of IL-1R1 and IL-1RacP compared to IL-1b non-sensitive AML samples, consistent with other findings demonstrating that expression of IL-1RAcP is a prognostic marker of AML [91][92][93]. In addition to relaying growth signals from IL-1 cytokines, a recent study suggested a broader role for IL-1RAcP in AML by amplifying oncogenic AML pathways through recruitment of the tyrosine kinases FLT3 and c-KIT in AML cells [92]. This suggests that therapeutic neutralization of IL-1RacP may permit to simultaneously target multiple oncogenic pathways in AML.…”
Section: Anti-tumorigenic Role Of Il-1b In Solid Tumourssupporting
confidence: 88%
“…Inflammation is frequently detectable in tumorigenic microenvironment, which exerts a fueling or restraining effect on tumorigenesis and therapeutic agent sensitivity (9,10). Recent studies indicate that, compared with normal hematopoietic counterparts, the leukemia cells in certain AML cases are highly proinflammatory (11,12), such as those characterized by the highly increased signaling activity of IL-1 superfamily members (13)(14)(15), which contributes to the modulation of the leukemic propagation in a context-dependent manner. In this regard, the IL-17 family represents a group of proinflammatory cytokines that play a pivotal role in numerous types of inflammatory diseases and cancers (16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Aberrant signaling via IL-1 and the downstream IRAK/TRAF pathway shared by IL-1R and Toll-like receptors has been implicated as a driver of survival and/or expansion of MDS and myeloid leukemia stem cells (LSC) (Agerstam et al, 2016;Askmyr et al, 2013;Barreyro et al, 2012;Carey et al, 2017;Muto et al, 2020;Smith et al, 2019;Zhang et al, 2016). Indeed, blockade of these pathways can limit and/or reverse disease progression (Carey et al, 2017;Mitchell et al, 2018;Rhyasen et al, 2013;Zhang et al, 2016). However, the mechanism(s) by which inflammatory signaling initiates expansion of oncogenically mutated HSC remain obscure.…”
Section: Discussionmentioning
confidence: 99%